Intra-Articular Calcaneus Osteoid Osteoma With an Ankle Varus and a Red-Brown Synovial Fluid in the Affected Joint, a Case Report - Dat Quoc Ngo; Thi Cao (SAGE Publishing, 2023)
Background: Only one article described ankle varus as a typical symptom in the late stage of the intra-articular osteoid osteoma of the calcaneus. And the red-brown color of synovial fluid in the affected joint hasn't been reported. This report shows a patient with intra-articular osteoid osteoma of the calcaneus who had the 2 above symptoms. Case presentation: A 39-year-old man had left ankle pain and the diagnosis was delayed for 20 months. At the late stage, the ankle was gradually varus. In our hospital, the withdrawal of the subtalar joint gave a red-brown synovial fluid. Together with the typical lesion on MRI, the diagnosis of intra-articular osteoid osteoma of the calcaneus was made. An open operation was performed for treatment. In the procedure, the red-brown synovial fluid was exuded. A specimen was harvested for biopsy confirming osteoid osteoma. Conclusions: It is still essential that intra-articular calcaneal osteoid osteoma should be considered in patients with prolonged pain and varus of the ankle. The red-brown synovial may be used as a finding for diagnosis.